A new destructive Poisson odd log-logistic generalized half-normal cure rate model. Issue 9 (3rd May 2019) - Pescim, Rodrigo R.; Ortega, Edwin M. M.; Suzuki, Adriano K.; Cancho, Vicente G.; Cordeiro, Gauss M.
ABSTRACT: We propose a new cure rate survival model by assuming that the initial number of competing causes of the event of interest follows a Poisson distribution and the time to event has the odd log-logistic generalized half-normal distribution. This survival model describes a realistic interpretation for the biological mechanism of the event of interest. We estimate the model parameters using maximum likelihood. For different sample sizes, various simulation scenarios are performed. We propose the diagnostics and residual analysis to verify the model assumptions. The potentiality of the new cure rate model is illustrated by means of a real data.